Non-perturbative solution for hydromagnetic flow over a linearly stretching sheet - Makinde, Oluwole D.; Mahabaleswar, U.S.; Maheshkumar, N. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the Adomian decomposition method with Padé approximants are integrated to study the boundary layer flow of a conducting fluid past a linearly stretching sheet under the action of a transversely imposed magnetic field. A closed form power series solution based on Adomian polynomials is obtained for the similarity nonlinear ordinary differential equation modelling the problem. In order to satisfy the farfield condition, the Adomian power series is converted to diagonal Padé approximants and evaluated. The results obtained using ADM-Padé are remarkably accurate compared with the numerical results. The proposed technique can be easily employed to solve a wide range of nonlinear boundary value problems.
Keywords: stretching sheet; hydromagnetic flow; ADM-Padé; numerical solutions